Development of a Culturally Contextualized Chemistry Literacy Test Based on West Kalimantan Culture on Thermochemistry Topics - Aisyah, Siti; Wiyarsi, Antuni (Faculty of Mathematics and Natural Sciences, Universitas Negeri Yogyakarta, 2025)
The aim of this research is to produce a chemical literacy assessment instrument based on cultural context for high school students on the topic of thermochemistry. The instrument development was carried out by constructing and validating the culturally contextualized chemical literacy test through the following stages: (1) identification of aspects and indicators of culturally based chemical literacy; (2) construction of the assessment instrument; (3) theoretical validation; (4) empirical validation; (5) reliability testing; and (6) difficulty level analysis. Data were analyzed using the Winsteps application and interpreted through the Rasch Model. The developed instrument consists of 12 items encompassing four chemical literacy indicators: Chemical Knowledge Concept, Chemistry in Context, Higher-Order Thinking Skills, and Attitude. The cultural context includes four West Kalimantan cultural themes: Dayak traditional tuak drinking, betel chewing tradition, nasi hadap-hadapan ceremony, and the karbit cannon festival. Validity was confirmed through Outfit MNSQ, Outfit ZSTD, and Point Measure Correlation (Pt. Mean Corr) values. Reliability analysis showed a Cronbach’s alpha of 0.56 (moderate), person reliability of 0.68 (moderate), and item reliability of 0.95 (very high). The instrument covers various difficulty levels: easy (1 item), moderate (9 items), and difficult (2 items), indicating a well-distributed test construction.